In Vivo Post–Cardiac Arrest Myocardial Dysfunction Is Supported by Ca2+/Calmodulin-Dependent Protein Kinase II–Mediated Calcium Long-Term Potentiation and Mitigated by Alda-1, an Agonist of Aldehyde Dehydrogenase Type 2. Issue 13 (27th September 2016) - Woods, Christopher E.; Shang, Ching; Taghavi, Fouad; Downey, Peter; Zalewski, Adrian; Rubio, Gabriel R.; Liu, Jing; Homburger, Julian R.; Grunwald, Zachary; Qi, Wei; Bollensdorff, Christian; Thanaporn, Porama; et al.
Abstract : Background: Survival after sudden cardiac arrest is limited by postarrest myocardial dysfunction, but understanding of this phenomenon is constrained by a lack of data from a physiological model of disease. In this study, we established an in vivo model of cardiac arrest and resuscitation, characterized the biology of the associated myocardial dysfunction, and tested novel therapeutic strategies. Methods: We developed rodent models of in vivo postarrest myocardial dysfunction using extracorporeal membrane oxygenation resuscitation followed by invasive hemodynamics measurement. In postarrest isolated cardiomyocytes, we assessed mechanical load and Ca 2 + -induced Ca 2+ release (CICR) simultaneously using the microcarbon fiber technique and observed reduced function and myofilament calcium sensitivity. We used a novel fiberoptic catheter imaging system and a genetically encoded calcium sensor, GCaMP6f, to image CICR in vivo. Results: We found potentiation of CICR in isolated cells from this extracorporeal membrane oxygenation model and in cells isolated from an ischemia/reperfusion Langendorff model perfused with oxygenated blood from an arrested animal but not when reperfused in saline. We established that CICR potentiation begins in vivo. The augmented CICR observed after arrest was mediated by the activation of Ca 2+ /calmodulin-dependent protein kinase II (CaMKII). Increased phosphorylation of CaMKII, phospholamban, and ryanodine receptor 2 was detected in the postarrest period. Exogenous adrenergic activation in vivo recapitulated Ca 2+ potentiation but was associated with lesser CaMKII activation. Because oxidative stress and aldehydic adduct formation were high after arrest, we tested a small-molecule activator of aldehyde dehydrogenase type 2, Alda-1, which reduced oxidative stress, restored calcium and CaMKII homeostasis, and improved cardiac function and postarrest outcome in vivo. Conclusions: Cardiac arrest and reperfusion lead to CaMKII activation and calcium long-term potentiation, which support cardiomyocyte contractility in the face of impaired postarrest myofilament calcium sensitivity. Alda-1 mitigates these effects, normalizes calcium cycling, and improves outcome. Abstract : Supplemental Digital Content is available in the text.